Exploring the Impact of Quality Education Management on Pupils’ Academic Performance. A Case Study of Basic Schools in Ghana - Donkoh, Ruth; Lee, Wing On; Donkor, Josephine; Twerefoo, Portia Oware; Boateng, Solomon A.; Akotey, Martin Kudwo (International Journal of Educational Development in Africa)
Generally, research on educational management omits its impact on pupils’ academic performance in basic schools. This research fills this gap by assessing the effect of quality education management functions on the academic performance of pupils in government basic schools in Ghana. A questionnaire was used to obtain data from headteachers, teachers, pupils, and the Parents’ and Teacher Association, totalling 240 respondents from 15 schools in Accra-Ghana. The findings indicated that teachers’ effort has the highest impact on pupils’ academic performance among all the managerial function variables in the research. The research recommends that the Ghana government and educational stakeholders emulate Singapore’s system of teacher development, which has enabled them to achieve educational excellence acknowledged across the globe.